Meningkatkan Keterampilan Membaca Pemahaman Materi Cerita Fiksi Menggunakan Model Pemberani di SDN TERANTANG - Maimunah .; Dessy Dwitalia Sari (Jurnal Teknologi Pendidikan Dan Pembelajaran | E-ISSN : 3026-6629, 2023)
The problem that occurs is the low activity of students so that it also affects reading comprehension skills and student learning outcomes. This happens because of one-way learning, lack of student reading activities, monotonous learning and lack of use of varied learning models. To overcome these problems, it is necessary to innovate in learning by using the PEMBERANI learning model (Problem Based Learning), Numbered Head Together, Snowball Throwing). This study aims to determine teacher activity, increase student activity, improve reading comprehension skills and improve student learning outcomes. This research was carried out with the type of classroom action research carried out in 4 meetings with a total of 20 students. Data analysis techniques in the form of descriptive qualitative and quantitative. Based on the findings from the study it can be concluded that the combination of PEMBERANI learning models shows teacher activity was very good with a score of 26, very active student activity gained 90%, very skilled reading comprehension skills obtained 90% and student learning outcomes increased obtaining 95% of students who completed. Suggestions for school principals and teachers that the results of this study as an alternative learning in improving the quality of learning and student achievement.